Exploring Carbon Pricing in Developing Countries : A Macroeconomic Analysis in Ethiopia - Telaye, Andualem; Benitez, Pablo; Tamru, Seneshaw; Medhin, Haileselassie; Toman, Michael (World Bank, Washington, DC, 2019)
In response to a challenge from members of the Carbon Pricing Panel for the world to expand carbon pricing to cover 25 percent of global emissions by 2020, Ethiopia commissioned a carbon pricing study to obtain recommendations on the role and possible forms of carbon pricing policies in Ethiopia. The study summarized in this report is a collaborative effort by the Government of Ethiopia, the Ethiopian Development Research Institute (EDRI), and the World Bank to better understand the potential benefits and costs for Ethiopia with use of carbon pricing to reduce greenhouse gas (GHG) emissions. The study also investigates distributional impacts of carbon pricing and measures that can help address unwanted distributional impacts. The specific aims include supporting the Government of Ethiopia (GoE) in identifying policy actions, including carbon pricing, to achieve its GHG emission reduction targets; facilitating a dialogue among Ethiopian stakeholders on related policy instruments; and building analytical and technical capacity for GoE's future policy planning. Lessons from this analysis may also be useful for other low-income countries.